Direct radical sulfonylation at α-C(sp3)-H of THF with sodium sulfinates in aqueous medium. Issue 11 (14th March 2019) - Singh, Manjula; Yadav, Lal Dhar S.; Singh, Rana Krishna Pal
Graphical abstract: Highlights: Transition-metal-free one-pot approach to 2-alkyl/aryl THFs at rt. The direct radical sulfonylation at α-C(sp 3 )-H of THF in aqueous medium. Sodium sulfinates as a radical source. K2 S2 O8 as a mild radical initiator. Abstract: A direct transition-metal-free, convenient and highly regioselective synthesis of 2-alkyl/aryl sulfonyl tetrahydrofurans (THFs) has been achieved from THF and sodium sulfinates using K2 S2 O8 as a mild oxidant. This one-pot simple protocol involves an efficient radical cross coupling reaction in aqueous medium utilizing K2 S2 O8 as an inexpensive and easy to handle radical surrogate at room temperature.